Symposium on Taiwan: Preface - Editor, CJAL (Columbia Journal of Asian Law, 1989)
In the winter of 1979, the United States shifted diplomatic rela- tions from Taipei to Beijing. At that time, many international observers predicted that Taiwan’s economic and political stability as well as its international stature would decline. Yet, Taiwan’s economy is stronger now than it was ten years ago, with Taiwan’s treasury holding roughly 75 billion dollars in foreign exchange reserves, placing it third in the world behind Japan and West Germany. In international affairs, Taiwan is gaining formal diplomatic recognition from a number of countries that had never recognized it before or that had shifted relations to Beijing. Since the death of former Republic of China (ROC) President, Chiang Ching-kuo, internal politics have changed dramatically. First, in July 1987, the government of the ROC lifted martial law which had been in effect since 1948. Second, the Kuomintang (KMT), which had long presided over a one-party system, agreed to accept a multi-party system and to allow the opposition parties to compete with it for genuine political power. Increasingly open political debate and more searching and penetrating scholarly inquiry into the legitimacy of government policies and procedures have accompanied these changes by the KMT. Moreover, both domestic and foreign parties with economic interests in Taiwan are demanding greater economic and legal protection.